The role of aspirin desensitization in patients with aspirin-exacerbated respiratory disease (AERD) - Spies,Jonas Willian (2016)
ABSTRACT INTRODUCTION: Aspirin-exacerbated respiratory disease (AERD) consists of a classic tetrad: moderate/severe asthma, chronic rhinosinusitis, nasal polyps, and intolerance to aspirin or other nonsteroidal anti-inflammatory drugs. Clinical control with drugs, surgery, and desensitization are treatment options. OBJECTIVE: To evaluate the efficacy and tolerability of aspirin desensitization in patients with AERD. METHODS: Periodic symptom assessment and endoscopy in patients with AERD undergoing surgery who were desensitized. RESULTS: Seventeen patients were desensitized. Eight patients completed the desensitization and were followed for a minimum of a one-year period (mean 3.1 years). These patients showed improvement in all symptoms. Moreover, surgical reassessment was not indicated in any of these patients and there was a decrease in costs with medication and procedures. Eight patients did not complete desensitization, mainly due to procedure intolerance and uncontrolled asthma, whereas another patient was lost to follow-up. CONCLUSION: Aspirin desensitization, when tolerated, was effective in patients with AERD and with poor clinical/surgical response.